2017
DOI: 10.5194/npg-24-467-2017
|View full text |Cite
|
Sign up to set email alerts
|

Multistable slip of a one-degree-of-freedom spring-slider model in the presence of thermal-pressurized slip-weakening friction and viscosity

Jeen-Hwa Wang

Abstract: Abstract. This study is focused on multistable slip of earthquakes based on a one-degree-of-freedom spring-slider model in the presence of thermal-pressurized slip-weakening friction and viscosity by using the normalized equation of motion of the model. The major model parameters are the normalized characteristic displacement, U c , of the friction law and the normalized viscosity coefficient, η, between the slider and background plate. Analytic results at small slip suggest that there is a solution regime for… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
20
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(20 citation statements)
references
References 59 publications
0
20
0
Order By: Relevance
“…However, the main factors in influencing earthquake occurrences commonly are spatially heterogeneous and also vary with time. Thus, the recurrence times of earthquakes, especially large events, are not constant inferred either from observations (Ando, 1975;Sieh, 1981;Kanamori and Allen, 1986;Wang and Kuo, 1998;Wang, 2005;Sieh et al, 2008) or from modeling (Wang, 1995(Wang, , 1996Ward, 1996Ward, , 2000Wang and Hwang, 2001). Kanamori and Allen (1986) observed that faults with longer T R are stronger than those with shorter T R .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the main factors in influencing earthquake occurrences commonly are spatially heterogeneous and also vary with time. Thus, the recurrence times of earthquakes, especially large events, are not constant inferred either from observations (Ando, 1975;Sieh, 1981;Kanamori and Allen, 1986;Wang and Kuo, 1998;Wang, 2005;Sieh et al, 2008) or from modeling (Wang, 1995(Wang, , 1996Ward, 1996Ward, , 2000Wang and Hwang, 2001). Kanamori and Allen (1986) observed that faults with longer T R are stronger than those with shorter T R .…”
Section: Introductionmentioning
confidence: 99%
“…The one-, two-, three-, and few-body models with various friction laws have also been applied to approach fault dynamics (see Turcotte, 1992). The studies for various friction laws based on spring-slider models are briefly described below: (1) for rate-and state-dependent friction (e.g., Rice and Tse, 1986;Ryabov and Ito, 2001;Erickson et al, 2008Erickson et al, , 2011He et al, 2003;Mitsui and Hirahara, 2009;Bizzarri, 2012a;Abe and Kato, 2013;Kostić et al, 2013a;Bizzarri and Crupi, 2014;Franović et al, 2016); (2) for velocity-weakening friction (e.g., Carlson and Langer, 1989;Huang and Turcotte, 1992;Brun and Gomez, 1994;Wang and Hwang, 2001;Wang, 2003;Kostić et al, 2013b); (3) for simple static-dynamic friction (e.g., Abaimov et al, 2007;Hasumi, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The frictional force F (u, v) is controlled by several factors (see Wang, 2016, and cited references therein). An effect combined from temperature and fluids in a fault zone can result in thermal pressurization (abbreviated as TP hereafter) which would yield a shear stress (resistance) on the fault plane (Sibson, 1973;Lachenbruch, 1980;Rice, 2006;Wang, 2009Wang, , 2011Wang, , 2016Wang, , 2017aBizzarri, 2009). Rice (2006) proposed two end-member models of TP, i.e., the adiabatic undrained deformation (AUD) model and slip-on-aplane (SOP) model.…”
mentioning
confidence: 99%
“…One-body spring-slider model. In the figure, t, m, K, η, V p , σ n , F , u, and u o denote, respectively, the time, the mass of the slider, the spring constant, the damping coefficient, the driving velocity, the normal stress, the frictional force, displacement of the slider, and the equilibrium location of the slider (after Wang, 2016). SOP model cannot be associated with the wear process, the SOP model is not used in this study.…”
mentioning
confidence: 99%